do you mean 2^3. since it is read as 2 cube...

Log in to add a comment

do you mean 2^3. since it is read as 2 cube...

Log in to add a comment

The Brainliest Answer!

Pattern:

a³ + b³ ⇒ sum of the cubes (product)

Where a is the first term, and b is the last term

(a + b) (a² - ab + b²) ⇒ factors of the sum of two cubes

Therefore:

(a + b) ( a² - ab + b²) = a³ + b³

Example 1:

Product: x³ + 27

Find its factor: (Follow the pattern given above)

Example 2:

Find the sum of two cubes (product of (y + 2) (y² - 2y + 4)

Follow the pattern (a + b) (a² - ab + b²)

a = y

b = 2

a² = (y)² or y²

- ab = -(y)(2) or -2y

b² = (2)² or 4

a³ = y³

b³ = (2)³ or 8

Substitute:

(y + 2) (y² - 2y + 4) =